CHEMICAL EVALUATION OF WEED SEEDS MIXED WITH WHEAT GRAINS AT HARVEST - M. N. Abbas; S. A. Rana; M. Shahid; N. Rana; M. Mahmood-ul-Hassan; M. Hussain (Journal of Animal and Plant Sciences, 2012)
Phytochemical potential of fifteen weeds associated with wheat crop was evaluated. Qualitative and quantitative phytochemical analysis of weed seed extracts was made. Alkaloids, saponins, glycosides, terpenoids, anthraquinine, steroids, flavonoids and tannins were detected from the weed seeds. Tannins and alkaloids were in high concentration. Tannins ranged from 7.97 to 24.17%, alkaloids 0.88 to 4.00%, saponins 0.54 to 1.29% and flavonoids 3.91 to 15.55%.  Wheat weeds care medicianlly important but their phytochemical potential needs to be further investigated.
Keywords: Alkaloids; Biodiversity; Laxative; Tannins; Predator-Prey.